Clinical Implications of Body Mass Index in Metastatic Breast Cancer Patients Treated With Abemaciclib and Endocrine Therapy. (4th August 2020) - Franzoi, Maria Alice; Eiger, Daniel; Ameye, Lieveke; Ponde, Noam; Caparica, Rafael; De Angelis, Claudia; Brandão, Mariana; Desmedt, Christine; Di Cosimo, Serena; Kotecki, Nuria; Lambertini, Matteo; Awada, Ahmad; et al.
Abstract: Background: There are limited data regarding the impact of body mass index (BMI) on outcomes in advanced breast cancer, especially in patients treated with endocrine therapy (ET) + cyclin-dependent kinase 4/6 inhibitors. Methods: A pooled analysis of individual patient-level data from MONARCH 2 and 3 trials was performed. Patients were classified according to baseline BMI into underweight (<18.5 kg/m 2 ), normal (18.5-24.9 kg/m 2 ), overweight (25-29.9 kg/m 2 ), and obese (≥30 kg/m 2 ) and divided into 2 treatment groups: abemaciclib + ET vs placebo + ET. The primary endpoint was progression-free survival (PFS) according to BMI in each treatment group. Secondary endpoints were response rate, adverse events according to BMI, and loss of weight (≥5% from baseline) during treatment. Results: This analysis included 1138 patients (757 received abemaciclib + ET and 381 placebo + ET). There was no difference in PFS between BMI categories in either group, although normal-weight patients presented a numerically higher benefit with abemaciclib + ET ( Pinteraction  = .07). Normal and/or underweight patients presented higher overall response rate in the abemaciclib + ET group compared with overweight and/or obese patients (49.4% vs 41.6%, odds ratio = 0.73, 95% confidence interval = 0.54 to 0.99) as well as higher neutropenia frequency (51.0% vs 40.4%, P = .004). Weight loss was more frequent in the abemaciclib + ET group (odds ratio = 3.23, 95% confidence interval = 2.09 to 5.01). Conclusions: Adding abemaciclib to ET prolongs PFS regardless of BMI, showing that overweight or obese patients also benefit from this regimen. Our results elicit the possibility of a better effect of abemaciclib in normal and/or underweight patients compared with overweight and/or obese patients. More studies analyzing body composition parameters in patients under treatment with cyclin-dependent kinase 4/6 inhibitors may further clarify this hypothesis.